2004
DOI: 10.2337/diacare.27.9.2217
|View full text |Cite
|
Sign up to set email alerts
|

Possible Impairment of Transcardiac Utilization of Adiponectin in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -Adiponectin, an adipocyte-derived protein, has been suggested to enhance insulin sensitivity and prevent atherosclerosis. Circulating adiponecin levels are reduced in states of insulin resistance such as type 2 diabetes. We examined transcardiac utilization of adiponectin in patients with and without type 2 diabetes. RESEARCH DESIGN AND METHODS-A total of 17 male type 2 diabetic patients and 17 male nondiabetic patients were investigated. Venous blood samples were taken to measure glucose and lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…13 Possible utilization of adiponectin in the coronary artery and/or heart has been described for non-diabetic patients based on a transcardiac gradient of adiponectin levels from aortic root to coronary sinus. 14 It is interesting that immunostaining for adiponectin was observed at the periphery of damaged cardiomyocytes in lesions at the granulative stage obtained from autopsied hearts with infarction. 15 In another immunohistochemical analysis, the boundaries of mouse hepatocytes were positive for adiponectin after 3 -6 h of carbon tetrachloride treatment, and the cytoplasm was intensely stained after 18 h of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…13 Possible utilization of adiponectin in the coronary artery and/or heart has been described for non-diabetic patients based on a transcardiac gradient of adiponectin levels from aortic root to coronary sinus. 14 It is interesting that immunostaining for adiponectin was observed at the periphery of damaged cardiomyocytes in lesions at the granulative stage obtained from autopsied hearts with infarction. 15 In another immunohistochemical analysis, the boundaries of mouse hepatocytes were positive for adiponectin after 3 -6 h of carbon tetrachloride treatment, and the cytoplasm was intensely stained after 18 h of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with other adipocyte-derived proteins, the circulating adiponectin level is reduced in patients with coronary artery disease and in states of insulin resistance such as obesity and type 2 diabetes (6−8). It has also been suggested that patients with type 2 diabetes not only have a decreased adiponectin level in the basal state but also impaired utilization of adiponectin in the tissue (9). Moreover, we have previously shown that hypoadiponectinemia is related to insulin resistance in essential hypertension, and that blockade of the renin-angiotensin system increases adiponectin levels with improvement in insulin sensitivity, at least in part via a decrease in adipocyte size (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, hypoadiponectinemia is considered as the cause of clustering of MS components through insulin resistance 49) and hypoadiponectinemia is known to be a useful marker of the pathogenesis of MS 18) . Furuhashi M et al 50) reported that decreased adiponectin concentration in coronary blood flow, estimated by simultaneous measurement of the aortic root and coronary sinus, reflected the severity of angiographical coronary atherosclerosis. This suggests that a high concentration of adiponectin exists in coronary blood flow, and adiponectin directly resists the progression of coronary atherosclerosis.…”
Section: Adiponectin and Plaque Instabilitymentioning
confidence: 99%